Activation Volumes in Tribochemistry; What Do They Mean and How to Calculate Them? - Hopper, Nicholas; Rana, Resham; Sidoroff, François; Cayer-Barrioz, Juliette; Mazuyer, Denis; Tysoe, Wilfred T. (Tribology letters, 2025)
Analyzing the effect of pressures and normal and shear stresses on chemical reaction rates, especially those occurring in a contact, remains the subject of controversy in the scientific community. This review article aims to clarify the principles that underpin the calculation of reaction rates based on transition-state theory (TST) and of activation volumes using a perturbation method of TST proposed by Evans and Polanyi. The goal is to aid researchers to calculate such tribochemical and mechanochemical parameters. In this paper, the fundamental ideas behind the calculation of reaction rates in chemistry are outlined. This article describes how TST is used to account for the large numbers of molecules involved in chemical reactions. The effects of individual stresses, and combination of normal and shear stresses on tribochemical reaction rates can be understood using a thermodynamics analysis. These concepts are illustrated by two examples of normal-stress-modified processes from results in the literature: homogeneous-phase Diels–Alder reactions and the surface decomposition of adsorbed methyl thiolate species on copper. The paper then reviews how to analyze tribochemical processes, which depend on coupled normal and shear stresses, showing that the effective activation volume is composed of multiple elementary-process activation volumes. Compensation effects, in which the pre-exponential factors and the activation volumes are correlated have been found for tribochemical reactions and this arises naturally from the Evans–Polanyi analysis. Finally, the activation volumes themselves depend on the applied stresses due to molecular distortions and a method for gauging the magnitude of these effects is described. Graphical abstract